Pengaruh E-Booklet tentang Buah Nanas untuk Mengatasi Dismenorea terhadap Peningkatan Pengetahuan Remaja Putri - Safitri, Safitri; Hayati, Fatihatul; Maharani, Sri (Jurnal Akademika Baiturrahim Jambi, 2024)
Adolescence is a transition period of secondary physical and sexual growth, one of which is menstruation. The prevalence of menstrual pain in Indonesia reaches 98.8% in adolescence. Menstrual pain affects daily activities both physically and emotionally. Non-pharmacological therapy is often used to treat dysmenorrhoea because it is safe, easy to obtain and has no side effects, one of which is pineapple. Pineapples contain the enzyme bromelain which provides analgesic and anti-inflammatory effects to relieve dysmenorrhoea. E-booklet is an educational media that contains writing and images combined to make it interesting for readers. This study aims to determine effect of e-booklet about pineapple for treating dysmenorrhoea on increasing the knowledge of adolescence girls in MAN 1 Muaro Jambi. This research is a quasi-experimental research with a one group pretest-posttest design. The population in this study were all adolescence girls in MAN 1 Muaro Jambi, with a total sample of 27 adolescence girls, using proportional random sampling techniques. Data was collected using online questionnaire March 2023. Data collected was analyzed using the T-Test. Results showed that there was an effect of e-booklet about pineapple to overcome dysmenorrhoea on increasing the knowledge of adolescence girls. It is hoped that adolescence girls can use e-booklet an educational media.